The Effect of The SQ3R Method Using Beelinguapp on Student’s Literal Reading Comprehension - Rosiana Silfani; Wijayadi Wijayadi; Ro’ifah Ro’ifah (Journal of Educational Sciences, 2024)
The ability to read is always discussed and important in the teaching and learning process. This study aims to determine how to implement the SQ3R method using online applications namely Beelinguapp. Then how does it affect students' reading comprehension? The effect of this method can be positive or negative. The method used in this study is a quantitative one-group Pre-test Post-Test design, with the instruments used pre-test and post-test and an observation sheet. This research was conducted on second-semester students majoring in English Education Department at the Universitas Muhammadiyah Surabaya. test score data were analyzed using SPSS ver. 26. The results of the mean in the Pre-Test is 59.67 and the mean in the Post-Test is 80.89. In addition, the result score of the mean in analysis N-Gain is 1.640. It showed that the application of the SQ3R method assisted by the use of online applications Beelinguapp could improve and has a positive effect on students' reading comprehension.